2021
DOI: 10.1029/2021jd034735
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Eddy‐Covariance and Flux‐Gradient Size‐Resolved Dust Fluxes During Wind Erosion Events

Abstract: Estimating accurately dust emission flux during aeolian erosion events is crucial for quantifying the amount of dust in the atmosphere. The rare existing field experiments quantifying such flux were mainly performed using the flux‐gradient (FG) method. Here, we present the first intercomparison of the size‐resolved dust fluxes estimated by both the FG and the eddy‐covariance (EC) methods during several erosion events. Both methods were applied simultaneously during the WIND‐O‐V (WIND erOsion in presence of spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(43 citation statements)
references
References 63 publications
2
39
2
Order By: Relevance
“…Regarding this last consideration, a reassuring point for the gradient method is that, when comparing it with eddy‐correlation measurements, Dupont et al. (2021) showed that both methods lead overall to similar dust fluxes, at least in the small and medium size classes (i.e., between 0.37 and 3.65 μm) to which the eddy‐covariance methods applies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding this last consideration, a reassuring point for the gradient method is that, when comparing it with eddy‐correlation measurements, Dupont et al. (2021) showed that both methods lead overall to similar dust fluxes, at least in the small and medium size classes (i.e., between 0.37 and 3.65 μm) to which the eddy‐covariance methods applies.…”
Section: Methodsmentioning
confidence: 99%
“…A second concern is that Dupont (2020) showed that the underlying assumption of the gradient method applied Year/doy Begin End to dust, namely that turbulent transport of particles was similar to that of momentum (Gillette et al, 1972), could be challenged because of the intermittency of the dust production compared to the more continuous absorption of momentum by the surface. Regarding this last consideration, a reassuring point for the gradient method is that, when comparing it with eddy-correlation measurements, Dupont et al (2021) showed that both methods lead overall to similar dust fluxes, at least in the small and medium size classes (i.e., between 0.37 and 3.65 μm) to which the eddy-covariance methods applies.…”
Section: Size-resolved Vertical Mass Fluxmentioning
confidence: 99%
“…The EC method allows to estimate a local dust flux at the height where both the wind velocity and the dust concentration fluctuations are measured, while the FG method estimates a dust flux in a fluid layer between the two OPCs. Compared to the FG method, the EC method has the advantage of estimating the dust flux with less hypotheses and independent of the estimation of the friction velocity, thermal stability, and stability corrections (Dupont et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…K20 applied a 23% concentration difference criteria on the 1.15‐μm size class only, allowing other size classes to reach lower concentration difference than 23%, while the uncertainty on this difference was not lower for other size classes. This uncertainty was higher for the coarse particle size classes (Dupont et al., 2021). Consequently, their criteria led them to accept points with near‐zero differences of coarse particle concentration between the two dust levels, overestimating φ fine .…”
Section: Influence Of Thermal Stratification On the Vertical Transfer...mentioning
confidence: 98%
See 1 more Smart Citation